Fitting and bag with fitting
A fitting tool made from a resin composition with thermoplastic olefin elastomer, maleic anhydride-modified polyolefin, and cellulose powder addresses the issue of synthetic resin waste by reducing plastic use while ensuring rigidity and toughness, with improved durability and water resistance.
Patent Information
- Application Number
- JP2021180029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-11-04
AI Technical Summary
Existing packaging materials with fittings, such as those used in bags, rely heavily on synthetic resins, contributing to plastic waste, and there is a need for a solution that reduces synthetic resin use while maintaining rigidity and toughness.
A fitting tool composed of a pair of band-shaped members made from a resin composition containing thermoplastic olefin elastomer, maleic anhydride-modified polyolefin, and cellulose powder, with a cellulose powder content exceeding 50% by mass, and optionally including a thermoplastic resin layer on the surface, to reduce synthetic resin usage.
The solution effectively reduces synthetic resin use, maintains rigidity and toughness, and enhances durability and water resistance, while allowing repeated opening and closing without chipping.
Smart Images

Figure 0007609757000005 
Figure 0007609757000006 
Figure 0007609757000007
Abstract
Description
[Technical Field]
[0001] The present invention relates to a fitting and a bag with a fitting. [Background technology]
[0002] Bags with fittings, in which a fitting that can be freely opened and closed is attached to the inner surface of the bag body near the opening, are widely used as packaging materials in various fields such as food, medicine, and miscellaneous goods. Examples of fittings include a pair of strip-shaped base materials, each having a first fitting portion and a second fitting portion that are provided on opposing surfaces of the base material along the longitudinal direction of the base material and that can be detachably fitted to each other.
[0003] The bag body is generally made of a thermoplastic resin. The material of the fitting is required to have moldability that allows the first and second fitting portions to be molded, and appropriate rigidity and toughness to allow the first and second fitting portions to be detachably fitted together. From these perspectives, polypropylene resin is generally used as the material for the fitting.
[0004] In recent years, waste from synthetic resin products has become a major issue, including the problem of marine plastics. As a result, there is an increasing demand every year to reduce the amount of synthetic resin used in synthetic resin products, especially packaging materials that are discarded immediately after use, by replacing at least a portion of the raw materials with materials other than synthetic resin. As raw materials other than synthetic resins, for example, cellulose materials such as paper are used.
[0005] Patent Document 1 proposes a packaging bag for medicated patches, in which a resealable means such as a zipper tape is provided on a package formed by heat-sealing a laminate of a specific layer configuration including a base layer, and also proposes using paper for the base layer. However, even if paper is used for the base layer, the reduction rate of the amount of synthetic resin used in the packaging bag of Patent Document 1 is not so large. It should be noted that Patent Document 1 does not particularly consider the material of the zipper tape. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-074484 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention aims to provide a fitting that can reduce the amount of synthetic resin used in a bag with a fitting, while still having rigidity and toughness that makes it usable as a fitting, and a bag with a fitting that uses the same. [Means for solving the problem]
[0008] The present invention has the following aspects. [1] A pair of strip-shaped first and second fitting members is provided, the first fitting member includes a strip-shaped first base material and a first fitting portion provided along a longitudinal direction on an opposing surface of the first base material; a fitting device, wherein the second fitting member includes a strip-shaped second base material and a second fitting portion provided on an opposing surface of the second base material along a longitudinal direction thereof and adapted to be detachably fitted with the first fitting portion; The fitting includes a thermoplastic resin and cellulose powder, the proportion of the cellulose powder relative to the total mass of the fitting is more than 50 mass%, and the average particle size of the cellulose powder is 20 μm or less, The first substrate and the second substrate are made of a resin composition (X) containing a thermoplastic resin including a thermoplastic olefin-based elastomer and a maleic anhydride-modified polyolefin, and the cellulose powder, and the proportion of the cellulose powder to the total mass of the resin composition (X) is more than 50 mass%. [2] The first fitting member and the second fitting member are Further, the film has a resin layer made of a resin composition (Y) containing a thermoplastic resin, The fitting according to [1], wherein the resin composition (Y) does not contain the cellulose powder or contains the cellulose powder in an amount of 20 mass % or less relative to the total mass of the resin composition (Y). [3] The fitting according to [2], wherein the resin layer is provided on the surface of the first fitting member and the second fitting member opposite to the opposing surface. [4] The fitting according to [2], wherein the resin layer is provided on each of the opposing surfaces of the first fitting member and the second fitting member. [5] The fitting according to [2], wherein the resin layer is provided on both the opposing surfaces of the first fitting member and the second fitting member and on the surface opposite to the opposing surfaces. [6] The fitting according to [4] or [5], wherein no chipping occurs when the fitting is repeatedly opened and closed 100 times. [7] A fitting according to any one of [2] to [6], wherein the rate of mass increase, expressed by the following formula, when the fitting is immersed in water at 23°C for 60 minutes is 105% or less. Mass increase rate (unit: %) = W 1 / W 0 ×100 (In the formula, W 0 is the mass before immersion, W 1 indicates the mass after immersion.) [8] The fitting according to any one of [1] to [7], wherein the resin composition (X) has a maximum stretch ratio of 270% or more. [9] The fitting according to any one of [1] to [8], wherein the resin composition (X) has a flexural modulus of 100 to 270 MPa.
[10] A bag body with a fitting, comprising a bag body for accommodating contents and any one of the fittings [1] to [9] attached to the inner surface of the bag body.
[11] The bag with a fitting according to
[10] , wherein the proportion of the cellulose powder to the total mass of the bag with a fitting is more than 50 mass%. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a fitting that can reduce the amount of synthetic resin used in a bag with a fitting and yet has the rigidity and toughness to be usable as a fitting, and a bag with a fitting that uses this fitting. [Brief explanation of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view showing an example of a fitting according to the present invention. [Figure 2] FIG. 10 is a schematic cross-sectional view showing another example of the fitting of the present invention. [Figure 3] FIG. 10 is a schematic cross-sectional view showing another example of the fitting of the present invention. [Figure 4] 1 is a schematic front view showing an example of a bag body with a fitting according to the present invention. [Figure 5] 5 is a schematic perspective view showing the state in which the bag with fitting of FIG. 4 is opened. FIG. DETAILED DESCRIPTION OF THE INVENTION
[0011] [Fittings] The fitting device of the present invention comprises a pair of belt-shaped first and second fitting members. The first fitting member comprises a belt-shaped first base material and a first fitting portion provided along the longitudinal direction on the opposing surface of the first base material. The second fitting member comprises a belt-shaped second base material and a second fitting portion provided along the longitudinal direction on the opposing surface of the second base material and adapted to detachably fit with the first fitting portion. The fitting of the present invention contains a thermoplastic resin and cellulose powder, and the proportion of the cellulose powder relative to the total mass of the fitting is more than 50 mass %. In the fitting of the present invention, the first and second substrates are made of a resin composition (X) containing a thermoplastic resin including a thermoplastic olefin elastomer and a maleic anhydride-modified polyolefin, and cellulose powder, the proportion of the cellulose powder being more than 50% by mass relative to the total mass of the resin composition (X). The fitting of the present invention is attached to the inner surface of the bag body that contains the contents. By attaching the fitting of the present invention to the inner surface of the bag body so as to fit along the opening formed in the bag body, the opening can be closed freely.
[0012] Examples of fittings according to the present invention will be described below with reference to the drawings. Note that the dimensions of the drawings shown in the following description are merely examples, and the present invention is not necessarily limited to these, and can be modified as appropriate within the scope of the present invention.
[0013] <First embodiment> As shown in FIG. 1, the fitting 10 of this embodiment comprises a pair of strip-shaped first fitting member 12 and second fitting member 14. The first fitting member 12 comprises a strip-shaped first base material 16 and a first fitting portion 18 consisting of a protruding male fitting portion provided along the longitudinal direction on an opposing surface 16a of the first base material 16. The first base material 16 and the first fitting portion 18 are integrally molded. The second fitting member 14 includes a strip-shaped second base material 20 and a second fitting portion 22 provided along the longitudinal direction on the opposing surface 20a of the second base material 20 and consisting of a female fitting portion that detachably fits into the first fitting portion 18. The second base material 20 and the second fitting portion 22 are integrally molded.
[0014] When the fitting 10 is attached to the bag body, the first side edge 16b of the first substrate 16 and the first side edge 20b of the second substrate 20 are attached to the opening side formed in the bag body, and the second side edge 16c of the first substrate 16 and the second side edge 20c of the second substrate 20 are attached to the content side of the bag body.
[0015] The first fitting portion 18 is provided on the opposing surface 16a of the first base material 16 along the longitudinal direction of the first base material 16. The first fitting portion 18 includes a stem 18a that rises from the opposing surface 16a of the first base material 16, and a head 18b that is provided at the tip of the stem 18a and has a generally semicircular cross section that is larger than the stem 18a.
[0016] The second fitting portion 22 is provided on the opposing surface 20a of the second base material 20 along the longitudinal direction of the second base material 20. The second fitting portion 22 is made up of a first arm portion 22a and a second arm portion 22b that rise up from the opposing surface 20a of the second base material 20 in an arc-shaped cross section, and a recess 22c is formed by the first arm portion 22a and the second arm portion 22b.
[0017] The first fitting portion 18 and the second fitting portion 22 can be detachably fitted together by fitting the head portion 18b of the first fitting portion 18 into the recessed portion 22c of the second fitting portion 22. The cross-sectional shapes of the first fitting portion 18 and the second fitting portion 22 may be any shape that allows the opening of the bag body to be repeatedly opened and closed by attaching and detaching the first fitting portion 18 and the second fitting portion 22 to each other, and any known cross-sectional shape may be adopted.
[0018] The thickness of the first substrate 16 is preferably 0.1 to 0.4 mm, and more preferably 0.12 to 0.3 mm. If the thickness of the first substrate 16 is equal to or greater than the lower limit, sufficient seal strength can be obtained when the fitting 10 is heat-sealed to the bag body. If the thickness of the first substrate 16 is equal to or less than the upper limit, sufficient flexibility can be obtained. A preferred embodiment of the thickness of the second substrate 20 is the same as a preferred embodiment of the thickness of the first substrate 16. The thicknesses of the first substrate 16 and the second substrate 20 may be the same or different.
[0019] The width of first substrate 16 is preferably 2 to 60 mm, and more preferably 3 to 40 mm. If the width of first substrate 16 is equal to or greater than the lower limit, sufficient seal strength can be obtained when fitting 10 is heat-sealed to the bag body. If the width of first substrate 16 is equal to or less than the upper limit, handling is easy and the fitting is less likely to deform during distribution and storage. The preferred embodiment of the width of the second substrate 20 is the same as the preferred embodiment of the width of the first substrate 16 . The width of the first substrate 16 and the width of the second substrate 20 may be the same or different.
[0020] The first substrate 16, the first fitting portion 18, the second substrate 20, and the second fitting portion 22 are made of a resin composition (X). The resin composition (X) will be described in detail later. The resin compositions (X) forming the first substrate 16, the first fitting portion 18, the second substrate 20, and the second fitting portion 22 may be the same or different.
[0021] Since the first substrate 16, the first fitting portion 18, the second substrate 20, and the second fitting portion 22 are made of the resin composition (X), the fitting 10 contains cellulose powder and a thermoplastic resin. The proportion of cellulose powder to the total mass of the fitting 10 is more than 50% by mass, preferably more than 53% by mass. If the proportion of cellulose powder is equal to or greater than the above lower limit, the amount of synthetic resin used in the bag with fitting is effectively reduced. Furthermore, sufficient rigidity is achieved even with a small proportion of thermoplastic resin. Furthermore, the proportion of cellulose powder relative to the total mass of fitting 10 is preferably 85 mass% or less, more preferably 75 mass% or less, even more preferably 65 mass% or less, and particularly preferably 56 mass% or less. If the proportion of cellulose powder is equal to or less than the above upper limit, fitting 10 will have better toughness.
[0022] (Resin composition (X)) The resin composition (X) contains cellulose powder and a thermoplastic resin. The thermoplastic resin contains a thermoplastic olefin elastomer (hereinafter also referred to as "TPO") and a maleic anhydride-modified polyolefin (hereinafter also referred to as "MA-PO"). TPO contributes to the toughness of the resin composition (X). MA-PO functions as a compatibilizer. When the thermoplastic resin contains MA-PO, the cellulose powder becomes more easily dispersed in the thermoplastic resin.
[0023] The average particle size of the cellulose powder is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. If the average particle size is equal to or less than the above upper limit, the moldability and toughness of the resin composition will be superior. The average particle size of the cellulose powder is preferably at least 5 μm. If the average particle size is at least the lower limit, the rigidity of the resin composition will be superior. The average particle size is measured by a laser diffraction particle size distribution measuring device.
[0024] The cellulose powder can be produced by using, for example, pulp derived from refined, highly pure cotton linters, wood, bamboo, bagasse, etc., and pulverizing the pulp using a grinder such as a knife mill, a vertical roller mill, or a jet mill to obtain powdered pulp as a raw material, and then classifying the pulp to obtain a desired average particle size. Commercially available cellulose powder may be used, such as KC Flock manufactured by Nippon Paper Industries Co., Ltd. and Cellulose Microfiber manufactured by Rettenmeyer Japan Co., Ltd.
[0025] Examples of TPO include propylene-ethylene copolymer thermoplastic elastomers, ethylene-propylene-diene terpolymer thermoplastic elastomers, etc. Among these, propylene-ethylene copolymer thermoplastic elastomers are preferred in terms of moldability and toughness. One type of TPO may be used alone, or two or more types may be used in combination. The ethylene content in the propylene-ethylene copolymer thermoplastic elastomer is preferably 1 to 30 mass %, more preferably 5 to 25 mass %, based on the total mass of all monomers constituting the propylene-ethylene copolymer thermoplastic elastomer.
[0026] The MFR of the TPO is preferably 5 to 20 g / 10 min, more preferably 9 to 16 g / 10 min. When the MFR of the TPO is at least the lower limit, the rigidity of the resin composition (X) is superior, and when it is at most the upper limit, the toughness and moldability of the resin composition (X) are superior. The MFR of TPO is measured in accordance with JIS K 6922-1 (ASTM D1238) at a temperature of 190°C and a load of 2.16 kg (21.18 N). In the case of a mixture containing two or more TPOs, the above-mentioned preferred range of MFR is the range of MFR of the mixture. The MFR of a mixture of two or more components (constituents) is calculated from the MFR of each component and the blending ratio (mass%). Specifically, it is calculated based on the following formula: log(MFR of mixture) = w1log(MFR1) + w2log(MFR2) + ... + w i log(MFRi)+…+wn log(MFRn) (In the formula, w i is the mass fraction of component i, MFRi is the MFR of component i, n is the total number of components in the mixture, and w1+w2+…+w i +...w n =1.)
[0027] The melting point of the TPO is preferably 50 to 160°C, more preferably 50 to 100°C. When the melting point of the TPO is not less than the above lower limit, the toughness is superior, and when it is not more than the above upper limit, the rigidity is superior. When two or more TPOs are used, the preferred melting point ranges are the respective melting point ranges. Melting points are measured by differential scanning calorimetry (DSC).
[0028] The flexural modulus of the TPO is preferably from 5 to 50 MPa, more preferably from 5 to 15 MPa. When the flexural modulus of the TPO is within the above range, the flexural modulus of the resin composition (X) is likely to fall within the preferred range described below. When the TPO is a mixture containing two or more TPOs, the preferred flexural modulus ranges are the respective flexural modulus ranges. The flexural modulus is measured in accordance with JIS K 7171 under conditions of a temperature of 23°C and a relative humidity of 50%.
[0029] Examples of MA-PO include an α-olefin-maleic anhydride copolymer, a mixture of an α-olefin polymer and maleic anhydride, and a mixture of an α-olefin, an α-olefin-maleic anhydride copolymer and maleic anhydride. Examples of the α-olefin include ethylene and propylene. One type of MA-PO may be used alone, or two or more types may be used in combination.
[0030] The melt viscosity of the MA-PO is preferably 100 to 15,000 mPa·s, more preferably 100 to 8,000 mPa·s, and even more preferably 100 to 1,000 mPa·s. When the melt viscosity of the MA-PO is at least the above-mentioned lower limit, the toughness and moldability are superior, and when it is at most the above-mentioned upper limit, the rigidity is superior. When two or more types of MA-PO are used, the preferred melt viscosity ranges are the melt viscosity ranges of each of them. The melt viscosity is measured by a capillary rheometer.
[0031] The acid value of MA-PO is preferably 5 to 150 mgKOH / g, more preferably 95 to 110 mgKOH / g. When the acid value of MA-PO is equal to or greater than the above-mentioned lower limit, the moldability is superior, and when it is equal to or less than the above-mentioned upper limit, the appearance is superior. When two or more types of MA-PO are used, the above-mentioned acid value range is preferably the range of each of the acid values. The acid number is measured by neutralization titration.
[0032] The melting point of the MA-PO is preferably low, for example, preferably 60 to 140° C., more preferably 60 to 80° C. When two or more types of MA-PO are contained, the preferred melting point ranges are the respective melting point ranges. Melting points are measured by differential scanning calorimetry (DSC).
[0033] The resin composition (X) may further contain other thermoplastic resins other than those described above, as necessary. Examples of other thermoplastic resins include polyethylene and polyurethane. Furthermore, the resin composition (X) may contain a thermoplastic resin composition containing a known metal soap (for example, the metal soap-containing composition described in Japanese Patent No. 3014273) or a fatty acid amide as a lubricant.
[0034] The resin composition (X) may further contain other components in addition to the cellulose powder and the thermoplastic resin, as necessary, such as additives such as stabilizers, antioxidants, antistatic agents, and colorants.
[0035] The proportion of cellulose powder relative to the total mass of the resin composition (X) is more than 50% by mass, preferably more than 53% by mass. When the proportion of cellulose powder is equal to or greater than the above lower limit, the amount of synthetic resin used in the bag with fitting is effectively reduced. Furthermore, sufficient rigidity is achieved even with a small proportion of thermoplastic resin. The proportion of cellulose powder relative to the total mass of resin composition (X) is preferably 85 mass% or less, more preferably 75 mass% or less, even more preferably 65 mass% or less, and particularly preferably 60 mass% or less. When the proportion of cellulose powder is equal to or less than the upper limit, the toughness and moldability of resin composition (X) are better.
[0036] The proportion of the thermoplastic resin relative to the total mass of the resin composition (X) is less than 50 mass%, preferably 47 mass% or less. When the proportion of the thermoplastic resin is equal to or less than the upper limit, the amount of synthetic resin used in the bag with a fitting is effectively reduced. The proportion of the thermoplastic resin relative to the total mass of the resin composition (X) is preferably 15% by mass or more, more preferably 25% by mass or more, even more preferably 35% by mass or more, and particularly preferably 40% by mass or more. When the proportion of the thermoplastic resin is equal to or more than the above lower limit, the toughness and moldability of the resin composition (X) are better.
[0037] The proportion of TPO relative to the total mass of resin composition (X) is preferably 10% by mass or more, more preferably 15% by mass or more. When the proportion of TPO is equal to or more than the above lower limit, the toughness and moldability of resin composition (X) are superior. The proportion of TPO relative to the total mass of resin composition (X) is preferably less than 40 mass%, more preferably less than 36 mass%. When the proportion of TPO is equal to or less than the above upper limit, the rigidity of resin composition (X) is superior.
[0038] The proportion of MA-PO relative to the total mass of resin composition (X) is preferably at least 1 mass%, more preferably at least 3 mass%, and even more preferably at least 5 mass%. When the proportion of MA-PO is at least the above lower limit, the toughness and moldability of resin composition (X) are better. Furthermore, the proportion of MA-PO relative to the total mass of resin composition (X) is preferably less than 15 mass%, more preferably less than 13 mass%, and even more preferably less than 11 mass%. When the proportion of MA-PO is equal to or less than the above upper limit, the rigidity and appearance of resin composition (X) are superior.
[0039] Resin composition (X) is preferably one in which the proportion of cellulose powder is more than 50% by mass and not more than 75% by mass, the proportion of TPO is 10% by mass or more and less than 40% by mass, and the proportion of MA-PO is 3% by mass or more and less than 15% by mass, relative to the total mass of resin composition (X). Resin composition (X) is more preferably one in which the proportion of cellulose powder is more than 50% by mass and not more than 60% by mass, the proportion of TPO is 15% by mass or more and less than 36% by mass, and the proportion of MA-PO is 5% by mass or more and less than 11% by mass.
[0040] The proportion of the other thermoplastic resin relative to the total mass of the resin composition (X) is preferably 0 mass % or more and less than 10 mass %, more preferably 0 mass % or more and less than 5 mass %.
[0041] The proportion of other components relative to the total mass of the resin composition (X) is preferably 0 mass % or more and less than 5 mass %, more preferably 0 mass % or more and less than 2 mass %.
[0042] The maximum stretching ratio of the resin composition (X) is preferably 270% or more, more preferably 270 to 500%. When the maximum stretching ratio of the resin composition (X) is 270% or more, the toughness of the resin composition (X) is superior, and cracks are less likely to occur in the first fitting portion 18 and the second fitting portion 22 when the resin composition (X) is attached or detached. Furthermore, if the maximum stretching ratio of the resin composition (X) is within the above range, the moldability is good, and the first fitting portion 18 and the second fitting portion 22 can be easily molded. The maximum stretching ratio is determined by the following method. Using a capillary rheometer, a sample (resin composition (X)) is melted and extruded through a die at a temperature of 170°C and an extrusion speed of 10 mm / min. The extruded molten material is taken up by a take-up roll via a pulley while gradually increasing the take-up speed from 1 m / min. The take-up speed at which the molten material breaks at the die outlet is taken as the maximum take-up speed, and the maximum draw ratio is calculated using the following formula. The acceleration of the take-up speed is 0.1 m / min. 2 The detailed measurement method is as described in the Examples below. Maximum draw ratio = Maximum take-up speed (mm / min) / Extrusion speed (mm / min) (for example, if the maximum take-up speed is 2 m / min (2 × 10 3 mm / min), maximum stretching ratio = 2 × 10 3 / 10=200.)
[0043] The flexural modulus of the resin composition (X) is preferably 100 to 270 MPa, more preferably 100 to 150 MPa. When the flexural modulus is equal to or greater than the lower limit, the resin composition (X) has better rigidity, and when it is equal to or less than the upper limit, the resin composition (X) has better toughness. The flexural modulus is measured in accordance with JIS K 7171 under conditions of a temperature of 23°C, a relative humidity of 50%, and a test speed of 1 mm / min ±20%.
[0044] The tensile yield stress of the resin composition (X) is preferably 4 to 13 MPa, more preferably 4 to 9 MPa. When the tensile yield stress is equal to or greater than the lower limit, the toughness and moldability are superior, and when it is equal to or less than the upper limit, the rigidity is superior. The tensile yield stress is measured in accordance with JIS K 7161-1 under the conditions of a temperature of 23°C, a relative humidity of 50%, and a test speed of 50 mm / min ±10%.
[0045] (Manufacturing method) The method for manufacturing the fitting 10 is not particularly limited except that the resin composition (X) is used as the material for forming the first base material 16, the first fitting portion 18, the second base material 20, and the second fitting portion 22, and any known method can be used. For example, cellulose powder and MA-PO are mixed, the resulting mixture is melt-kneaded with TPO, and if necessary, other thermoplastic resins and other components to obtain a resin composition (X), and the resulting resin composition (X) is molded to obtain the first fitting member 12 or the second fitting member 14. The mixing method may be dry mixing using a super mixer, a Henschel mixer or the like. Examples of the melt-kneading method include a method in which the raw materials are fed into a melt-kneading machine such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader, or a mixing roll, and melt-kneaded. Examples of molding methods include extrusion molding, injection molding, inflation molding, and vacuum molding.
[0046] The fitting of the present invention is not limited to the fitting 10 described above. In the fitting device of the present invention, the first fitting member and the second fitting member may further have a resin layer made of a resin composition (Y) containing a thermoplastic resin. The resin composition (Y) does not contain cellulose powder or contains 20 mass % or less of cellulose powder relative to the total mass of the resin composition (Y). The cellulose powder used in the resin composition (Y) is the same as the cellulose powder used in the resin composition (X).
[0047] <Second embodiment> Fig. 2 shows an example in which a seal layer made of resin composition (Y) is provided on the surface opposite to the opposing surfaces of the first fitting member and the second fitting member. The same parts in Fig. 2 as those in Fig. 1 are designated by the same reference numerals, and their explanations will be omitted. The fitting 10A illustrated in FIG. 2 is the same as fitting 10, except that the first fitting member 12 has a first seal layer 26 laminated on the outer surface 16d side of the first substrate 16, and the second fitting member 14 has a second seal layer 30 laminated on the outer surface 20d side of the second substrate 20.
[0048] In the fitting 10A, the resin composition (X) constituting the first base material 16, the first fitting portion 18, the second base material 20, and the second fitting portion 22 has a higher ratio of cellulose powder to the total mass of the resin composition (X) than the ratio of cellulose powder to the total mass of the fitting 10A. The preferred ratio of cellulose powder to the total mass of the fitting 10A is the same as that of the fitting 10 of the first embodiment. The preferred ranges of the maximum draw ratio, flexural modulus and tensile yield stress of the resin composition (X) are the same as those in the first embodiment.
[0049] The first seal layer 26 and the second seal layer 30 are made of a resin composition (Y). The resin composition (Y) contains a thermoplastic resin. Examples of the thermoplastic resin include linear low-density polyethylene, high-pressure low-density polyethylene, high-density polyethylene, polypropylene, ethylene-(meth)acrylic acid alkyl ester copolymer, ethylene-α-olefin copolymer, olefin elastomer, styrene elastomer, acid-modified olefin resin, ethylene-vinyl acetate copolymer, and ionomer. The resin composition (Y) may contain known additives such as stabilizers, antioxidants, lubricants, antistatic agents, and colorants, if necessary. Examples of lubricants include fatty acid amides such as ethylene bisstearic acid amide, stearic acid amide, palmitic acid amide, and oleic acid amide, polyethylene wax, stearic acid, etc. These lubricants may be used alone or in combination of two or more. When the resin composition (Y) contains cellulose powder, the resin composition (X) may be used as the compound containing cellulose.
[0050] The proportion of cellulose powder relative to the total mass of resin composition (Y) is 20% by mass or less, preferably 10% by mass or less, or may be zero. If the proportion of cellulose powder is equal to or less than the above upper limit, sufficient heat seal strength with the bag body can be obtained, and delamination between the fitting portion and the bag body is less likely to occur when the bag body with the fitting is handled.
[0051] The thickness of the first seal layer 26 is preferably 0.01 to 0.2 mm, and more preferably 0.02 to 0.1 mm. If the thickness of the first seal layer 26 is equal to or greater than the lower limit, sufficient seal strength can be obtained when the fitting is heat-sealed to the bag body. If the thickness of the first seal layer 26 is equal to or less than the upper limit, sufficient flexibility can be obtained. In addition, the proportion of cellulose powder to the total mass of the fitting 10 can be increased. The preferred embodiment of the thickness of the second sealing layer 30 is the same as the preferred embodiment of the thickness of the first sealing layer 26 .
[0052] (Manufacturing method) The method for manufacturing fitting 10A is not particularly limited, and any known method can be used, except that resin composition (X) is used as the material for forming first base material 16, first fitting portion 18, second base material 20, and second fitting portion 22, and resin composition (Y) is used as the material for forming first seal layer 26 and second seal layer 30. For example, co-extrusion molding can be used. The mixing method, melt-kneading method, and molding method are the same as those in the first embodiment.
[0053] In the fitting 10A, the mass ratio (Y) / (X) of the resin composition (X) constituting the first substrate 16, first fitting portion 18, second substrate 20, and second fitting portion 22 to the resin composition (Y) constituting the first seal layer 26 and second seal layer 30 is preferably 1 / 99 to 40 / 60, more preferably 10 / 90 to 30 / 70. When the mass ratio of Y is 40% by mass or less, sufficient moldability and stretchability are obtained even when the cellulose powder content exceeds 50% by mass. Furthermore, when the mass ratio of Y is 10% or more, sufficient heat seal strength is obtained between the fitting and the layer of the bag to be joined.
[0054] According to this embodiment, by providing a resin layer (sealing layer) on the surface opposite to the opposing surfaces of the first fitting member and the second fitting member, productivity is improved when extruding the fitting, as shown in the examples described below. Furthermore, the provision of the resin layer (sealing layer) improves the water resistance of the fitting, as will be shown in the examples below. Specifically, a fitting can be obtained in which the mass increase rate when the fitting is immersed in water at 23°C for 60 minutes is 105% or less.
[0055] <Third embodiment> 3 shows an example in which a seal layer made of resin composition (Y) is provided on the surface opposite to the opposing surfaces of the first fitting member and the second fitting member, and a surface layer is further provided on the opposing surfaces of the first fitting member and the second fitting member. The same parts in FIG. 3 as those in FIGS. 1 and 2 are designated by the same reference numerals, and their explanations will be omitted. The fitting 10B illustrated in FIG. 3 is the same as the fitting 10A of the second embodiment, except that the first fitting member 12 has a first surface layer 46 laminated on the opposing surface 16a side of the first substrate 16, and the second fitting member 14 has a second surface layer 40 laminated on the opposing surface 20a side of the second substrate 20.
[0056] In the fitting 10B, the resin composition (X) constituting the first base material 16, the first fitting portion 18, the second base material 20, and the second fitting portion 22 is one in which the ratio of cellulose powder to the total mass of the resin composition (X) is higher than the ratio of cellulose powder to the total mass of the fitting 10B. The preferred ratio of cellulose powder to the total mass of the fitting 10B is the same as that of the fitting 10 of the first embodiment. The preferred ranges of the maximum draw ratio, flexural modulus and tensile yield stress of the resin composition (X) are the same as those in the first embodiment.
[0057] In this embodiment, the resin composition (Y) constituting the first seal layer 26 and the second seal layer 30 will be referred to as "resin composition (Ys)", and the resin composition (Y) constituting the first surface layer 46 and the second surface layer 40 will be referred to as "resin composition (Yh)". In fitting 10B, resin compositions (Ys) and (Yh) may be the same or different. In this embodiment, preferred thermoplastic resins for the resin composition (Ys) include known thermoplastic resins for use in sealing layers. Examples include linear low-density polyethylene, high-pressure low-density polyethylene, high-density polyethylene, polypropylene, ethylene-(meth)acrylic acid alkyl ester copolymer, ethylene-α-olefin copolymer, olefin elastomer, styrene elastomer, acid-modified olefin resin, ethylene-vinyl acetate copolymer, and ionomer. Preferred thermoplastic resins for the resin composition (Yh) include polyethylene resins such as low-density polyethylene, linear low-density polyethylene, and high-density polyethylene, polypropylene resin, ethylene-vinyl acetate copolymer, and ionomer, which are commonly used as materials for fittings.
[0058] The thickness of the first surface layer 46 is preferably 0.01 to 0.2 mm, and more preferably 0.01 to 0.1 mm. If the thickness of the first surface layer 46 is equal to or greater than the lower limit, chipping is less likely to occur in the fitting portion when the fitting portion is repeatedly opened and closed. If the thickness of the first surface layer 46 is equal to or less than the upper limit, sufficient moldability and extensibility can be obtained even if the blending ratio of cellulose powder to the total mass of the fitting 10 is increased. Furthermore, the ratio of cellulose powder to the total mass of the fitting 10 can be increased. The preferred embodiment of the thickness of second surface layer 40 is the same as the preferred embodiment of the thickness of first surface layer 46 .
[0059] (Manufacturing method) The method for manufacturing fitting 10B is not particularly limited, and any known method can be used, except that resin composition (Yh) is used as the material for forming first surface layer 46 and second surface layer 40, resin composition (X) is used as the material for forming first base material 16, first fitting portion 18, second base material 20, and second fitting portion 22, and resin composition (Ys) is used as the material for forming first seal layer 26 and second seal layer 30. For example, co-extrusion molding can be used. The mixing method, melt-kneading method, and molding method are the same as those in the first embodiment.
[0060] In fitting 10B, the mass ratio of resin composition (Yh), resin composition (X), and resin composition (Ys), (Yh) / (X) / (Ys), is preferably 1-39 / 60-98 / 1-39, and more preferably 5-15 / 70-90 / 5-15. In the above mass ratios, the sum of (Yh), (X), and (Ys) is 100.
[0061] According to this embodiment, a resin layer (sealing layer) is provided on the surface opposite to the opposing surfaces of the first fitting member and the second fitting member, and a resin layer (surface layer) is further provided on the opposing surfaces of the first fitting member and the second fitting member, thereby improving productivity when extruding the fitting device, as will be shown in the examples described below. Furthermore, the provision of the sealing layer and surface layer improves the water resistance of the fitting, as will be shown in the examples described later. Specifically, a fitting can be obtained whose mass increase rate when immersed in water at 23°C for 60 minutes is 105% or less, preferably 103% or less, and most preferably 100%.
[0062] Furthermore, according to this embodiment, the durability of the fitting is improved by providing a resin layer (surface layer) on the opposing surfaces of the first fitting member and the second fitting member. For example, as will be shown in the examples below, it is possible to obtain a fitting that does not develop chips in the fitting portions (first fitting portion and second fitting portion) even when the fitting is repeatedly opened and closed 100 times. Furthermore, as will be shown in the examples below, it is possible to obtain a fitting in which the reduction in fitting strength when the fitting is repeatedly opened and closed 100 times is 5% or less, preferably 3% or less, and most preferably 0%.
[0063] In the fittings of the second and third embodiments, one or more other layers may be provided between the first substrate and the first sealing layer or between the second substrate and the second sealing layer. Examples of such other layers include a barrier layer and an adhesive layer. Examples of materials for the barrier layer include polyvinyl alcohol. Examples of materials for the adhesive layer include ethylene-vinyl acetate copolymer. Furthermore, in the fitting of the third embodiment, the first seal layer 26 and the second seal layer 30 may not be provided.
[0064] Furthermore, the first and second fitting portions in the fitting device of the present invention are not limited to a combination of a male fitting portion and a female fitting portion. For example, the first and second fitting portions may each have a plurality of parallel male fitting portions, and the heads of the male fitting portions may be inserted between two opposing male fitting portions to hook them together for attachment and detachment.
[0065] [Bag with fitting] The bag with a fitting of the present invention comprises a bag body that contains contents, and the fitting of the present invention attached to the inner surface of the bag body. The bag with fitting of the present invention can adopt any known form other than that it is provided with the fitting of the present invention.
[0066] As an example of the bag with a fitting of the present invention, a bag with a fitting 1 (hereinafter referred to as "bag 1") equipped with the above-mentioned fitting 10 will be described below. As shown in FIG. 4, the bag body 1 of this embodiment comprises a sealed bag body 50 for containing contents, and a fitting 10 attached laterally to the inner surface of the upper part of the bag body 50.
[0067] The bag body 50 is formed by overlapping a first film material 52 and a second film material 54 and heat-sealing their entire peripheral edges 56 to form a sealed bag body 50. A cutting assist line 58 is provided in the horizontal direction above the fitting 10 on the bag body 50, and a notch 60 is formed at the end of the line.
[0068] The fitting 10 has an outer surface 16d of the first base material 16 of the fitting 10 welded to the first film material 52 of the bag body 50, and an outer surface 20d of the second base material 20 of the fitting 10 welded to the second film material 54 of the bag body 50. The fitting 10 is attached so that the first side edge 16b of the first base material 16 and the first side edge 20b of the second base material 20 face the opening side, and the second side edge 16c of the first base material 16 and the second side edge 20c of the second base material 20 face the content side.
[0069] In this embodiment, the shape of the bag body 50 is rectangular. However, the shape of the bag body 50 is not limited to a rectangle. In addition, the size of the bag body 50 is not particularly limited, and may be selected appropriately depending on the contents to be accommodated in the bag body 50.
[0070] The first film material 52 and the second film material 54 that form the bag body 50 may be any material that can heat-seal the fitting 10, and may be, for example, a single-layer film consisting of only a sealant layer, or a laminated film having at least a sealant layer and a base layer, with the sealant layer being one of the outermost layers (the inner surface side of the bag body). The laminated film may further have a functional layer such as a barrier layer.
[0071] Examples of the sealant layer include linear low-density polyethylene, high-pressure low-density polyethylene, high-density polyethylene, ethylene-(meth)acrylic acid alkyl ester copolymer, unstretched polypropylene, ethylene-vinyl acetate copolymer, and ionomer. The thickness of the sealant layer is preferably 0.01 to 0.05 mm, more preferably 0.01 to 0.02 mm. If the thickness of the sealant layer is equal to or greater than the lower limit, sufficient sealing strength can be obtained. If the thickness of the sealant layer is equal to or less than the upper limit, the synthetic resin content of the bag body 1 can be reduced.
[0072] Examples of the substrate layer include paper, biaxially oriented nylon, and biaxially oriented polypropylene. Paper containing pulp is preferred as the base material layer from the viewpoint of reducing the synthetic resin content of the bag body 1. Examples of paper containing pulp include fine paper, art paper, coated paper, pure white roll paper, single-sided gloss bleached kraft paper, special double-sided bleached kraft paper, and bleached kraft paper. The paper weight is 40 to 100 g / m 2 is preferable, and 50 to 70 g / m 2 is more preferred. An example of a laminated film having a paper substrate layer is laminated paper.
[0073] The cutting assist line 58 is a line that assists in cutting the bag body 50 above the fitting 10 to open it. Examples of the cutting assist line 58 include a weakened line formed by thinning the first film material 52 and the second film material 54 of the bag body 50 at the portion corresponding to the cutting assist line 58 compared to the remaining portions, a weakened line formed by perforations, and a weakened line formed by rows of small holes. Furthermore, the cutting assist line 58 is not limited to the weakened line described above, and may be a line formed by printing or the like that indicates the position to cut with scissors, a cutter, or the like. In this embodiment, the cutting assistance line 58 is formed along the horizontal direction of the bag body 50, but is not limited to this form and may be formed at an angle to the width direction of the bag body 50.
[0074] The shape of the notch 60 is triangular in this example, but is not particularly limited thereto, and may be semicircular, linear, or the like. The bag body 1 can be manufactured by a known method except for using the fitting 10.
[0075] When opening the bag body 1, the upper part of the bag body 50 is cut and removed from the notch 60 along the cutting assist line 58, forming an opening 62 at the top, as shown in Fig. 5, and the bag can be opened. The opening 62 formed in the bag body 1 can be repeatedly opened and closed by attaching and detaching the first fitting portion 18 and the second fitting portion 22 of the fitting 10.
[0076] The bag with fitting of the present invention is not limited to the bag 1 described above. For example, the bag with fitting of the present invention may be a bag with fitting equipped with a fitting of the present invention other than the above-described fitting 10. Specifically, instead of fitting 10, the bag with fitting may be equipped with fitting 10A of the second embodiment or fitting 10B of the third embodiment.
[0077] Furthermore, the bag body of the bag with a fitting is not particularly limited, and various forms of bag bodies known as bag bodies of bags with a fitting can be used. For example, bag body 1 is a sealed bag until it is opened using cutting assist line 58, but it may also be a bag with a fitting having a bag body with an opening formed in advance. [Example]
[0078] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. "Parts" means "parts by mass."
[0079] [Raw materials] The raw materials used in this example are listed below. (Resin composition (X)) TPO1: ExxonMobil "Vistamaxx 6102FL", propylene-ethylene copolymer thermoplastic elastomer, ethylene content 16% by mass, MFR = 3 g / 10 min, melting point 55°C, density 0.862 g / cm 3 , flexural modulus 14MPa. TPO2: ExxonMobil "Vistamaxx 8880", propylene-ethylene copolymer thermoplastic elastomer, ethylene content 6 mass%, MFR = 10,000 g / 10 min, melting point 97°C, density 0.879 g / cm 3 . MA-PO1: Mitsubishi Chemical's "Diakaruna 30M", an olefin wax (α-olefin-maleic anhydride copolymer 66.8% by mass, α-olefin polymer 32.9% by mass, maleic anhydride 0.3% by mass), melting point 70-76°C, melt viscosity 140-210 mPa·s (measured at 100°C), acid value 95-110 mgKOH / g. MA-PO2: Sanyo Chemical Industries, Ltd. "UMEX 1010", α-olefin-maleic anhydride copolymer, melting point 135°C, melt viscosity 6000 mPa·s (measured at 160°C), acid value 52 mgKOH / g. PO1: "AP-600P" manufactured by Katsuta Chemical Industry Co., Ltd., an olefin-based masterbatch (lubricant) containing metal soap. The cellulose powders used were KC Floc W-06MG manufactured by Nippon Paper Industries Co., Ltd. and ARBOCEL UFC-100 manufactured by Rettenmeyer Co., Ltd. The average particle size of each cellulose powder was measured using a laser diffraction particle size distribution analyzer (Malvern dry particle size distribution analyzer "MASTER SIZER 3000"), and the average particle size of W-06MG was 6 μm, and the average particle size of UFC-100 was 10 μm. (Comparative resin) PP: Random polypropylene (homo), MFR = 3 g / 10 min, density 894 kg / m 3 .
[0080] (Resin composition (Ys)·(Yh)) PE1: Low-density polyethylene, MFR = 5 g / 10 min, melting point 108 °C, density 0.921 g / cm 3 . (Resin composition (Ys)) PE2: Linear low-density polyethylene, MFR = 11 g / 10 min (190 °C, load 2.16 kg), density 0.914 g / cm 3 . PO2: Ethylene-α-olefin copolymer, MFR = 8 g / 10 min, melting point 68°C, density 0.880 g / cm 3 . Aliphatic amides: lubricants, oleic acid amide. Cellulose compound: the same composition as the resin composition (X) in Example 8.
[0081] (Evaluation method) [Dispersibility] Pellets of resin composition (X) were injection molded at a temperature of 150 to 180°C to obtain a sheet-like test piece having a thickness of 3 mm. A part of the obtained test piece was cut with a microtome, and the cross section was observed under a microscope and evaluated according to the following criteria. ○: No aggregates with a maximum diameter of 50 μm or more exist within a randomly selected 100 mm × 100 mm area. ×: Aggregates with a maximum diameter of 50 μm or more are present in a randomly selected area of 100 mm × 100 mm.
[0082] [Zipper formability] In producing the fittings, if the fittings could be molded without any problems, it was marked with ◎ (good molding), if the fittings could be molded but were difficult to remove during extrusion molding, resulting in low production efficiency, it was marked with ○ (molding possible), and if defects occurred in the fitting parts (first fitting part, second fitting part), strip-shaped base material (first base material, second base material), surface layer, or sealing layer, it was marked with × (molding impossible).
[0083] [Maximum stretching ratio] The maximum draw ratio of the pellets of resin composition (X) was determined in accordance with JIS K 7199 using a Capillograph (capillary rheometer) manufactured by Toyo Seiki Seisakusho Co., Ltd., according to the following procedure. 1. Pellets of the resin composition are filled into a cylinder with a die installed at the outlet and heated to 170°C to melt them. 2. The piston is lowered from the entrance of the cylinder at a constant speed of 10 mm / min. This causes the melt to be extruded from the die outlet with a diameter of 1 mm at a speed of 10 mm / min. 3. The strand-like molten material extruded from the die is passed through a pulley and clamped between take-up rolls. 4. Start the take-up roll speed at 1 m / min and gradually increase it. The acceleration of the take-up speed is 0.1 m / min. 2 Let's say. 5. Record the take-up speed when the melt at the die exit is cut off. 6. Repeat the above steps 1 to 5 a total of three times (N=3), and use the minimum recorded take-up speed as the maximum take-up speed to calculate the maximum draw ratio using the following formula. Maximum draw ratio = Maximum take-up speed (mm / min) / Extrusion speed (mm / min) In addition, items for which the withdrawal speed could not be measured were marked as "unacceptable."
[0084] [Flexural modulus] Pellets of resin composition (X) were injection molded at a temperature of 150 to 180°C to obtain a sheet with a thickness of 3 mm, which was then cut into a width of 25±0.5 mm and a length of 60±3 mm to obtain a test piece. The flexural modulus of the obtained test piece was measured in accordance with JIS K 7171 under conditions of a temperature of 23°C, a relative humidity of 50%, and a test speed of 1 mm / min±20%.
[0085] Tensile yield stress Pellets of resin composition (X) were injection molded at 170°C to obtain a sheet having a thickness of 3 mm, and then a 1B-type test piece was cut out in accordance with JIS K 7161-2. The tensile yield stress of the obtained test piece was determined in accordance with JIS K 7161-1 under the conditions of a temperature of 23°C, a relative humidity of 50%, and a test speed of 50 mm / min ± 10%.
[0086] <Durability test> [Chip occurrence] The manufactured fittings were repeatedly opened and closed up to 100 times. Every 5 times, the fitting was observed under a microscope, and the number of times when chipping was observed was recorded. The test was terminated when chipping was observed.
[0087] [Mating strength reduction rate] The prepared fittings were cut into 5cm lengths to prepare test pieces. Five test pieces were each repeatedly opened and closed 100 times. The fitting strength R 1 (unit: N / 5mm) and mating strength R after 100 times opening 100 The fitting strength reduction rate (unit: N / 5mm) was measured using the following method, and the fitting strength reduction rate was calculated using the following formula. 100 , R 1 The average value of five test pieces was used for each. A larger value for the mating strength reduction rate means a greater reduction in mating strength due to repeated opening and closing. A mating strength reduction rate of 0% means that there was no change in mating strength between the first and 100th times. Fitting strength change rate (unit: %) = 100 - (R 100 / R 1 ×100)
[0088] [Method for measuring fitting strength] A sample 50 mm long was cut out from the part of the bag body where the fitting was attached in the longitudinal direction of the first fitting member and the second fitting member, and the first substrate and second substrate on the opening side were clamped in the chucks of a tensile testing machine, and the maximum strength measured when pulled at a pulling speed of 50 mm / min was taken as the fitting strength.
[0089] <Water resistance test> [Mass increase rate due to water absorption] The first fitting member having a male fitting portion (first fitting portion) was cut to a length of 10 cm to prepare a test specimen. To prevent water absorption from the cut surface, the cut surface was coated with resin (hot melt adhesive) using a glue gun. Mass W in advance 0 The test piece whose mass (before immersion) was measured was immersed in water at 23°C for 60 minutes, removed, and the surface was wiped with kitchen paper (non-woven fabric). 1 The mass increase rate was calculated using the following formula: Mass increase rate (unit: %) = W 1 / W 0 ×100 The mass gain rate was determined for six test pieces, and the average value of four pieces excluding the maximum and minimum values was recorded as the measurement result. A larger mass increase rate indicates a larger amount of water absorption. A mass increase rate of 100% means that the mass remained unchanged before and after the water absorption test, and it can be determined that no water absorption occurred.
[0090] [Examples 1 to 4, Comparative Examples 1 to 3] (Preparation of Resin Composition (X)) According to the formulation shown in Table 1, a resin composition (X) was prepared by the following procedure. First, cellulose powder and MA-PO were mixed to obtain a mixture. In Examples 1 and 3, a powdery mixture was obtained by mixing using a supermixer. In Examples 2 and 4, the mixture was melt-kneaded in a co-rotating twin-screw extruder at a molding temperature of 130 to 200°C and a screw rotation speed of 50 to 130 rpm, and extruded into strands with a diameter of 3 to 5 mm. The extruded mixture was then cut into pellets. Next, the obtained mixture and the remaining raw materials (TPO, PO) were melt-kneaded in a co-rotating twin-screw extruder under conditions of a molding temperature of 150 to 180°C and a screw rotation speed of 40 to 100 rpm, and extruded into strands having a diameter of 2 to 4 mm. The extruded mixture was then cut to obtain pellets of resin composition (X).
[0091] (Making fittings) The fitting shown in FIG. 1 was produced by the following procedure. A composite shaped die was prepared for forming a first fitting member having a male fitting portion and a second fitting member having a female fitting portion. Pellets of the resin composition (X) were melt-kneaded in a single-screw extruder at a molding temperature of 130 to 180°C, introduced into the composite shaped die for co-extrusion molding, then introduced into a cooling water bath for cooling and solidification, and wound up on a winder. The thickness of the first substrate and the second substrate was each 0.2 mm. The items shown in Table 1 were evaluated by the above evaluation methods. The evaluation results for each example are shown in Table 1. In the evaluation results in Table 1, "-" indicates that no measurement or evaluation was performed.
[0092] [Table 1]
[0093] [Examples 5 to 8] (Preparation of Resin Composition (X)) A resin composition (X) was prepared according to the formulation shown in Table 2. The resin compositions (X) used in Examples 5, 6, 7, and 8 were the same as the resin compositions (X) prepared in Examples 1, 2, 3, and 4, respectively.
[0094] (Preparation of Resin Composition for Seal Layer (Ys)) In Examples 5 to 7, pelletized PE1 was used as the resin composition for the seal layer (Ys). In Example 8, a resin composition for a seal layer (Ys) was prepared according to the formulation shown in Table 2. That is, a cellulose compound (resin composition (X) used in Example 8) and PE1 were melt-kneaded in a co-rotating twin-screw extruder at a molding temperature of 150 to 180°C and a screw rotation speed of 40 to 100 rpm, and extruded into strands with a diameter of 2 to 4 mm. The extruded mixture was then cut to obtain pellets of the resin composition for a seal layer (Ys). The content of cellulose powder relative to the total mass of the resin composition for the seal layer (Ys) was 5.3 mass %.
[0095] (Making fittings) The fitting shown in FIG. 2 was produced by the following procedure. A composite profile die was prepared for forming a first fitting member having a male mating portion and a second fitting member having a female mating portion. Pellets of resin composition (X) and pellets of resin composition (Ys) for the seal layer were melt-kneaded in a single-screw extruder at a molding temperature of 130 to 180°C. These were then co-extruded through the composite profile die, cooled and solidified in a cooling water bath, and wound up on a winder. The thicknesses of the first and second substrates were each 0.2 mm, and the thicknesses of the first and second seal layers were each 0.03 mm. The mass ratio of the resin composition (X) to the resin composition for the seal layer (Ys) in the entire fitting is shown in Table 2. Table 2 also shows the proportion of cellulose powder relative to the total mass of the fitting. The items shown in Table 2 were evaluated by the above evaluation methods. The evaluation results for each example are shown in Table 2.
[0096] [Table 2]
[0097] [Examples 9 to 11] (Preparation of Resin Composition (X)) A resin composition (X) was prepared according to the formulation shown in Table 3. The resin compositions (X) used in Examples 9, 10, and 11 were the same as the resin compositions (X) prepared in Examples 1, 2, and 3, respectively.
[0098] (Preparation of Resin Composition for Seal Layer (Ys)) According to the formulation shown in Table 3, a resin composition (Ys) was prepared by the following procedure. All raw materials were melt-kneaded in a co-rotating twin-screw extruder at a molding temperature of 150 to 180°C and a screw rotation speed of 40 to 100 rpm, extruded into strands with a diameter of 2 to 4 mm, and the extruded kneaded material was cut to obtain pellets of the resin composition (Ys) for the seal layer.
[0099] (Preparation of Surface Layer Resin Composition (Yh)) In Examples 9 to 11, pelletized PE1 was used as the surface layer resin composition (Yh).
[0100] (Making fittings) The fitting shown in FIG. 3 was produced by the following procedure. A composite profile die was prepared for forming a first fitting member having a male mating portion and a second fitting member having a female mating portion. Pellets of the surface layer resin composition (Yh), pellets of the resin composition (X), and pellets of the seal layer resin composition (Ys) were melt-kneaded in a single-screw extruder at a molding temperature of 130 to 180°C. These were then co-extruded through the composite profile die, cooled and solidified in a cooling water bath, and wound up on a winder. The thicknesses of the first and second substrates were each 0.2 mm, the first and second seal layers were each 0.03 mm, and the first and second surface layers were each 0.03 mm. The mass ratio of the surface layer resin composition (Yh), the resin composition (X), and the seal layer resin composition (Ys) in the entire fitting is shown in Table 3. Table 3 also shows the proportion of cellulose powder relative to the total mass of the fitting. The items shown in Table 3 were evaluated by the above evaluation methods. The evaluation results for each example are shown in Table 3.
[0101] [Table 3]
[0102] [Test example] The fittings obtained in Examples 1, 5, and 9 were subjected to durability tests and water resistance tests using the methods described above. The results of each example are shown in Table 4.
[0103] [Table 4]
[0104] As shown in Tables 1 to 3, in Examples 1 to 11, fittings containing more than 50% by mass of cellulose powder were obtained. In particular, Examples 5 to 8, in which a seal layer made of resin composition (Y) was provided, and Examples 9 to 11, in which a surface layer and a seal layer made of resin composition (Y) were provided, were excellent in zipper formability. Furthermore, the results in Table 4 show that the surface layer made of resin composition (Y) provides excellent durability of the fitting portion, and the surface layer and seal layer made of resin composition (Y) provide excellent water resistance. In the results of the water resistance test shown in Table 4, although the fittings of Examples 1 and 5 experienced an increase in mass due to water absorption, when the dimensions of the cross section perpendicular to the longitudinal direction were measured, no change in the cross-sectional dimensions was observed before and after water absorption. [Explanation of symbols]
[0105] 1. Bag body with fitting 10,10A,10B fitting tool 12 First fitting member 14 Second fitting member 16 First base material 18 First fitting part 20 Second base material 22 Second fitting part 26 First sealing layer 30 Second sealing layer 40 Second surface layer 46 1st surface layer 50 bags
Claims
1. A pair of band-shaped first and second fitting members is provided, The first fitting member includes a band-shaped first base material and a first fitting portion provided along a longitudinal direction of an opposing surface of the first base material, The second fitting member is a fitting device including a belt-shaped second base material and a second fitting portion provided along a longitudinal direction of an opposing surface of the second base material and removably fitted with the first fitting portion, The fitting includes a thermoplastic resin and cellulose powder, the ratio of the cellulose powder to the total mass of the fitting is more than 50 mass%, and the average particle size of the cellulose powder is 20 μm or less, The first substrate and the second substrate are made of a resin composition (X) containing a thermoplastic resin including a thermoplastic olefin-based elastomer and a maleic anhydride-modified polyolefin, and the cellulose powder, wherein the proportion of the cellulose powder to the total mass of the resin composition (X) is more than 50 mass%.
2. The first fitting member and the second fitting member include: Further, the film has a resin layer made of a resin composition (Y) containing a thermoplastic resin, The fitting according to claim 1 , wherein the resin composition (Y) does not contain the cellulose powder or contains the cellulose powder in an amount of 20 mass % or less relative to the total mass of the resin composition (Y).
3. 3. The fitting device according to claim 2, wherein the resin layer is provided on a surface of the first fitting member and a surface of the second fitting member opposite to the opposing surface.
4. The fitting according to claim 2 , wherein the resin layer is provided on each of the opposing surfaces of the first fitting member and the second fitting member.
5. 3. The fitting device according to claim 2, wherein the resin layer is provided on both the opposing surfaces of the first fitting member and the second fitting member and on a surface opposite to the opposing surfaces.
6. 6. The fitting according to claim 4, which is free from chipping when the fitting is repeatedly opened and closed 100 times.
7. The fitting according to any one of claims 2 to 6, wherein when the fitting is immersed in water at 23°C for 60 minutes, the mass increase rate represented by the following formula is 105% or less. Mass increase rate (unit: %) = W 1 / W 0 ×100 (In the formula, W 0 is the mass before immersion, W 1 indicates the mass after immersion.)
8. The fitting according to any one of claims 1 to 7, wherein the resin composition (X) has a maximum stretch ratio of 270% or more.
9. The fitting according to any one of claims 1 to 8, wherein the resin composition (X) has a flexural modulus of 100 to 270 MPa.
10. A bag body with a fitting comprising: a bag body for accommodating contents; and the fitting according to any one of claims 1 to 9 attached to an inner surface of the bag body.
11. The bag with fitting according to claim 10, wherein the proportion of the cellulose powder to the total mass of the bag with fitting is more than 50 mass%.
Citation Information
Patent Citations
Fastener and article provided with fastener
CN103188961A
Biodegradable bag
JP2001122289A
Fitting fastener and bag with fastener
JP2006055280A
Fiber composite material and method of producing the same
JP2013249341A
Package bag for skin patch
JP2016074484A